THE STATE OF TECHNICAL SUPPORT OF AGRICULTURAL PRODUCERS OF UKRAINE IN THE CONTEXT OF GLOBALIZATION - Шарко, Богдан (SWorldJournal, 2022)
Currently, most producers of the agar sector have significant problems with the implementation of logistics strategy in accordance with production needs and trends in innovation. Significant rise in price of means of production, imperfection of credit, in